PERFORMA BAKTERIPADATANAH TERCEMAR PESTISIDA - Maman Rahmansyah; Nunik Sulistinah (BERITA BIOLOGI, 2009)
Preliminary study on bacterial survive in soil containing pesticide has been carried out. Soil samples collected from Lembang and Dieng. The soil deprive from agriculture area that intensively using pesticide, and compared to other samples gathered from forest soil. All samples examined for total bacteria, denitrification bacteria, phosphate solubilizing bacteria, soil induce respiration, urease and phosphatase activities. Pattern of whole parameters in each soil sample configured similarly, but the value performed differently in the same parameters. Total bacterial population in soil samples also inspected after the samples amended with some certain pesticides. Survival bacteria subjected to media amended with insecticide (Propoxur, Diazinon, and Chlorpyrifos), and herbicides (Bromacil and 2,4-D), and correlation of bacterial growth between sample location were varied. Bacterial degrading pesticide particularly isolated from the soil samples containing 1000 ppm Curzate (fungiside) and 500 ppm 2,4-D.The isolates then cultured in the medium containing insecticide and herbicide, and the response on growth observed in 7 days incubation. Bacterial perform were meaningful to reference of soil degrading pesticide residue in agriculture soil; and it would make representative reference in an effort to use bacteria throughout biofertilizer improvement.